2007
DOI: 10.1597/06-128.1
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Nasometer Measuring the Temporal Characteristics of Nasalization

Abstract: The results suggest that the Nasometer can be used as a valid tool to measure the temporal characteristics underlying nasalization and confirm significant vowel effects on the temporal patterns of nasalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Instrumental assessment of velopharyngeal function is recommended for adequate management of VPD and may involve the use of nasometry to corroborate findings of speech nasality. While nasometric assessment provide a quantifiable measure of speech nasality and has been extensively studied and described in the literature (5)(6)(7) , the recommendation for not conducting nasometric assessment during use of CA is based on clinical impressions.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental assessment of velopharyngeal function is recommended for adequate management of VPD and may involve the use of nasometry to corroborate findings of speech nasality. While nasometric assessment provide a quantifiable measure of speech nasality and has been extensively studied and described in the literature (5)(6)(7) , the recommendation for not conducting nasometric assessment during use of CA is based on clinical impressions.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing HPC and LPC samples, it was observed that the set of HPC samples had a higher incidence of high vowels. Researchers have reported that different vowels produce significantly different patterns of nasality, with the height of the tongue influencing the acoustic characteristics of each sample and the degrees of perception of nasality (21) . Particularly, for individuals with hypernasality and repaired cleft palate, it was emphasized by some authors (21,22) that listeners perceive high vowels as more nasal than low vowels, both in isolation and in sentences.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that different vowels produce significantly different patterns of nasality, with the height of the tongue influencing the acoustic characteristics of each sample and the degrees of perception of nasality (21) . Particularly, for individuals with hypernasality and repaired cleft palate, it was emphasized by some authors (21,22) that listeners perceive high vowels as more nasal than low vowels, both in isolation and in sentences. A trend for the listeners in this study to perceive the set of HPC samples (with higher percentage of high vowels) as more nasal than the set of LPC samples with lesser percentage of high vowels therefore was expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a nasometer can confirm temporal patterns of nasalance, there are still controversies as to its use, results and interpretation. 2,3 There are different tests to evaluate the voice such as the GRBAS scale, the voice handicap index (VHI) scale, and the acoustic analysis of the voice among others. In the last decades the voice acoustic analysis has become essential in voice evaluation.…”
Section: Introductionmentioning
confidence: 99%